Granular cell tumor of the larynx – an unusual cause of the common symptoms - John, Joemol; Velayutham, Prabu; Kanakasabai, Sri M.; Vetrivel, Iswarya; Loganathan, Abinaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Granular cell tumors (GCTs), or Abrikossoff’s tumors, are rare neoplasms of neural origin, likely derived from Schwann cells. They typically affect the head and neck region, most commonly the tongue. Laryngeal involvement is uncommon, comprising 6–10% of cases. While most GCTs are benign, 1–2% may undergo malignant transformation. A 55-year-old female presented with hoarseness of voice for six months. Videolaryngoscopy revealed a single, sessile, pale pinkish mass with a smooth surface on the posterior half of the right true vocal cord, extending upto the right two-thirds of the posterior commissure. Vocal cords were mobile bilaterally. Laryngeal microsurgery was performed under general anesthesia. The mass extended inferiorly into the vocal process of the arytenoid, which was also excised. Histopathological examination confirmed a granular cell tumor, showing characteristic features including pseudoepitheliomatous hyperplasia of the overlying epithelium. Though rare, laryngeal granular cell tumors should be considered in patients presenting with glottic lesions and voice changes. Their histologic appearance can mimic squamous cell carcinoma, posing a diagnostic challenge. Awareness of this entity among otolaryngologists and pathologists is crucial for accurate diagnosis and appropriate management.